1981
DOI: 10.1007/bf00148460
|View full text |Cite
|
Sign up to set email alerts
|

Microeconomic theory and generalised cost

Abstract: In a number of articles in this journal the use of generalised cost in travel demand analysis and transport planning has been subject to debate. However, some of the fundamental problems raised in these articles are left unanswered -e.g., the precise relationship between conventional microeconomic consumer demand theory and generalised cost, an issue with which this article is concerned. It is shown here that necessary and sufficient conditions for expressing travel demand in terms of generalised cost are that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Bruzelius (1981) queried whether we had ''really shown that such models work?'' We have shown that they do not work.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bruzelius (1981) queried whether we had ''really shown that such models work?'' We have shown that they do not work.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to know whether GC is empirically valid because of the fact that GC is consistent with conventional microeconomic demand theory if and only if the willingness to pay to save travel time is not a function of real income (Bruzelius 1981). In addition to insights of a methodological nature, we also provide a range of results that are of broader interest for the purposes of forecasting, benchmarking and interpretation in the passenger rail market.…”
Section: Scope and Significancementioning
confidence: 98%
See 2 more Smart Citations
“…However, this does not take into account the physical network structure of transport modes or their different financial overheads, speeds, frequencies, levels of effort required in their use, interchange times and capacities [37,38]. Therefore, in this work the cost of travel is expressed as a generalized cost, taking into account both time and monetary components of any journey along the transport network in one unified value [39,40]. This makes the assumption that the cost of travel between an origin and destination can be generally expressed in the form:…”
Section: Measuring Transport Costs and Accessibilitymentioning
confidence: 99%